“We want our freedom back, that’s our only need”: a qualitative study of health and social needs among asylum seekers and undocumented migrants crossing the borders from Belarus to Lithuania - El Arab, Rabie Adel; Urbanavice, Rita; Jakavonyte-Akstiniene, Agne; Skvarcevskaja, Marija; Austys, Donatas; Briones-Vozmediano, Erica; Rubinat-Arnaldo, Esther; Istomina, Natalja (Frontiers in Public Health, 2024)
Background: The influx of undocumented migrants and asylum seekers into Lithuania, particularly during the COVID-19 pandemic, presents unique public health challenges. This study employs the Social Determinants of Health framework to explore the healthcare and social needs of this vulnerable population.Methods: In May 2022, we carried out a qualitative study through semi-structured interviews with asylum seekers across four centers in Lithuania. Employing both purposive and snowball sampling techniques, we selected participants for our investigation. The study comprised 21 interviews-19 conducted in Arabic and 2 in English-with durations ranging between 20 to 40 minutes each. We audio-recorded all interviews, transcribed them verbatim, and subsequently performed a thematic analysis using Atlas.ti software. This process of design and analysis strictly followed the principles of thematic analysis as outlined by Braun and Clarke, guaranteeing methodological precision and rigor.Findings: 21 interviews revealed critical insights into the healthcare access challenges, mental health issues, and social integration barriers faced by the participants. Key themes included 'Healthcare Needs and the Impact of the COVID-19 Pandemic ' and 'Social needs and Aspirations Amidst Pandemic-Induced Uncertainty '. The findings highlight the multifaceted healthcare and social needs of asylum seekers, juxtaposed against significant barriers they face.Access to medical services is hindered by long waiting times and financial constraints, especially for specialized care such as dental services. Communication issues during medical appointments due to language barriers and the lack of gender-specific healthcare, such as access to gynecological services, further exacerbate the challenges. Additionally, the COVID-19 pandemic introduces hurdles such as limited testing, isolation measures, language-specific information barriers, and insufficient social distancing practices. Mental health has emerged as a critical concern, with asylum seekers reporting significant stress and emotional exhaustion due to uncertainty and restrictive living conditions. Social needs extend to delayed asylum application processes, inconsistent language education opportunities, inadequate clothing, and nutrition that lacks cultural sensitivity, and living conditions characterized by overcrowding and insufficient facilities. The restricted freedom of movement within asylum seeking centres severely impacts their psychological well-being, underscoring a deep longing for autonomy and a better life despite the myriad of challenges faced.